Antimicrobial quaternary ammonium organosilane cross-linked nanofibrous collagen scaffolds for tissue engineering - Dhand, Chetna; Balakrishnan, Yamini; Ong, Seow Theng; Dwivedi, Neeraj; Venugopal, Jayarama Reddy; Harini, Sriram; Leung, Chak Ming; Low, Kenny Zhi Wei; Loh, Xian Jun; Beuerman, Roger W.; Ramakrishna, Seeram; Verma, Navin Kumar; et al. (Dovepress, 2018)
Introduction: In search for cross-linkers with multifunctional characteristics, the present work investigated the utility of quaternary ammonium organosilane (QOS) as a potential cross-linker for electrospun collagen nanofibers. We hypothesized that the quaternary ammonium ions improve the electrospinnability by reducing the surface tension and confer antimicrobial properties, while the formation of siloxane after alkaline hydrolysis could cross-link collagen and stimulate cell proliferation. Materials and methods: QOS collagen nanofibers were electrospun by incorporating various concentrations of QOS (0.1%–10% w/w) and were cross-linked in situ after exposure to ammonium carbonate. The QOS cross-linked scaffolds were characterized and their biological properties were evaluated in terms of their biocompatibility, cellular adhesion and metabolic activity for primary human dermal fibroblasts and human fetal osteoblasts. Results and discussion: The study revealed that 1) QOS cross-linking increased the flexibility of otherwise rigid collagen nanofibers and improved the thermal stability; 2) QOS cross-linked mats displayed potent antibacterial activity and 3) the biocompatibility of the composite mats depended on the amount of QOS present in dope solution – at low QOS concentrations (0.1% w/w), the mats promoted mammalian cell proliferation and growth, whereas at higher QOS concentrations, cytotoxic effect was observed. Conclusion: This study demonstrates that QOS cross-linked mats possess anti-infective properties and confer niches for cellular growth and proliferation, thus offering a useful approach, which is important for hard and soft tissue engineering and regenerative medicine.